AN APPROACH IN TEACHING WRITING SKILLS: DOES IT OFFER A NEW INSIGHT IN ENHANCING STUDENTS WRITING ABILITY - Indrilla, Nidya; Ciptaningrum, Dyah Setyowati (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This paper aims to reveal the effectiveness of Scientific Approach in the teaching writing skills. This research used a quasi-experimental design. The population was grade VIII students of Redion School. Two classes were randomly selected as the sample. They are class 8B which used Scientific Approach as the experimental group, while class 8D becomes the control group which used conventional approach. The data were collected by using writing test. The data were analyzed through descriptive and inferential statistics with the SPSS 20 for Windows computer program. The results were as follows: (1) there were significant differences in the writing achievement among the students taught by using the Scientific Approach and conventional approach, (2) the use of the Scientific Approach was more effective than that of the conventional approach in teaching writing skills.